COMPARATIVESTUDY OFMATHEMATICSLEARNING STUDENTS OUTCOMES TAUGHT BY COOPERATIVE LEARNING MODELTEAMS GAMES TOURNAMENTTYPE (TGT) ANDTALKING STICKTYPE(TS) - Jahring Jahring; Armiana Armiana; Akbar Nasrum (JME (Journal of Mathematics Education), 2017)
This research method was Experimental Research. The Research aimed at determining whether there were differences on the student learning outcomes taught by cooperative learning model Teams Games Tournament type (TGT) and the students who were taught by cooperative learning model Talking Stick type (TS). This research was conducted at class VIII SMP Negeri 2 Kolaka in the academic year 2016/2017 consisting of 8 classes with total students was 199 students. VIII5 Class was the first experimentalclass taught by cooperative learning model TGT type and VIII3 Class was the second experimental class taught by cooperative learning TS type. Technique of Data Analysis used descriptive statistics and inferential statistics. The research findings were: (1)Mathematics learning outcomes of students taught by cooperative learning model TGT type consisting of 28 students obtained mean = 81,29, median = 84, mode = 85, standarddeviation = 8,814, and variance = 77,693 . In addition, 23 of 28 students (82.15%) had learning outcomes above KKM = 75, and 19 of 28 students (57.14%) had scores above mean = 81.29. (2) The learning outcomes of mathematics student taught by cooperative learning model of TS type consisting of 28 students obtained mean = 81,64, median = 84,50, mode = 87, standard deviation = 9,306, and variance = 86,605. In addition, 22 of 28 students (78.57%) had learning outcomes above KKM = 75, and 20 of 28 students (71.42%) had scores above mean = 81.64. Based on the findings above, it can be concluded that there was no difference in the mean of mathematics learning outcomes of students taught by cooperative learning model both TGT type and TS type. The models provided good learning outcomes and improved the students’ engagement in the teaching and learning process.